Epidemiological characterization of dengue in Villa Clara, Cuba. 2020-2021 - Cepero-Montalván, Mireya (2025)
Dengue is a viral disease that is considered an arbovirus worldwide. As the number of cases is increasing worldwide and in Cuba, its management, control, and prevention continue to be a challenge. An observational, descriptive, longitudinal, and retrospective study was conducted in Villa Clara, Cuba, during 2020 and 2021, with the aim of characterizing dengue in Villa Clara during the period 2020-2021. The study population included all suspected cases of dengue from 2020 to 2021, according to the data contained in the computerized file of the Department of Statistics. Document analysis and descriptive statistics were used as methods, and risk stratification was also performed. In 2021, the highest rate of suspected dengue cases was observed, with the 19-24 and 10-14 age groups having the highest incidence for both sexes. Surveillance increased by 40.7%, as did reactivity in all municipalities. In 2020, 38.9% of reactive immunoglobulin M (IgM) tests were confirmed with immunoglobulin G (IgG). The municipalities of Placetas and Caibarién were located in the high-risk stratum. It is concluded that through stratification of entomoepidemiological risk, it is possible to identify higher-risk localities, which makes control strategies much more effective, provided that interventions are implemented simultaneously in localities that, due to their composition, can generate more cases and function as disseminating localities.